Pulsatile normothermic perfusion with cardiopulmonary bypass for thoracic organ recovery in donation after uncontrolled circulatory death: a feasible strategy for expanding the donor pool - Zeraatiannejaddavani, Sam; Shahrbaf, Mohammadamin; Kamalzadeh, Nazafarin; Shafikhani, Yazdan (Experimental and clinical transplantation, 2025)
Objectives: Donation after circulatory death offers a promising solution to expand the thoracic organ donor pool, yet its application remains limited because of warm ischemia and technical barriers, especially in uncontrolled donation after circulatory death. We aimed to evaluate a pulsatile normothermic car-diopulmonary bypass-based strategy for thoracic organ recovery of uncontrolled donors after circulatory death and the effects of this strategy on graft function and recipient outcomes. Materials and methods: In this prospective single-center study, we studied thoracic organs recovered from uncontrolled donors after circulatory death after ≥60 minutes of unsuccessful cardiopulmonary resuscitation. After heparinization and pharmacologic optimization, donors underwent median sternotomy and were connected to a cardiopulmonary bypass circuit with pulsatile flow. Organ assessment was performed in vivo. Donor, graft, and recipient functional data were recorded, with follow-up results studied through at least 1 year. Results: Forty-two donors were included. All hearts (n = 42) and 40 lungs (from 84 donors) were successfully transplanted. Despite prolonged cardiopulmonary resuscitation, no graft failure or recipient mortality occurred. One year survival for both heart and lung recipients was 100%. Heart grafts showed progressive improvement in functional status, including left ventricular ejection fraction, lactate levels, and New York Heart Association classification; lungs demonstrated sustained gains in gas exchange, pulmonary function tests, and 6-minute walk distance. Mild primary graft dysfunction (grade 1-2) occurred in 10% of lung recipients (all unilateral transplants). Pericardial effusion increased, likely because of trauma before procurement, but resolved without effects on function. Conclusions: Pulsatile normothermic cardiopulmonary bypass enables successful procurement of thoracic organs from uncontrolled donors after circulatory death with excellent outcomes. This low-cost physiological approach may offer a viable strategy to expand availability of donors in resource-limited settings.
Gesehen am 10.11.2025